Which Factors Increase Risk of Malalignment of the Hip-Knee-Ankle Axis in TKA? - Mullaji, Arun B. (Springer-Verlag, 2012)
BACKGROUND: Computer navigation has improved accuracy and reduced the percentage of alignment outliers in TKA. However, the characteristics of outliers and the risk factors for limb malalignment after TKA are still unclear. QUESTIONS/PURPOSES: We therefore addressed the following questions: (1) What is the incidence and characteristics of outliers for postoperative limb mechanical axis (hip-knee-ankle [HKA] angle outside the conventional 180° ± 3° range) and component alignment in TKA? And (2) what are the preoperative clinical or radiographic risk factors for limb mechanical axis malalignment in TKA? METHODS: We retrospectively reviewed the clinical and radiographic records of 1500 computer-assisted TKAs to identify outliers for postoperative HKA axis and component alignment and determined risk factors for malalignment. Full-length hip-to-ankle and knee radiographs were used to measure preoperative HKA angle, femoral coronal bowing, joint divergence angle, tibial subluxation, and tibial bone loss and postoperative HKA angle and femoral and tibial component angle. RESULTS: The incidence of outliers for postoperative limb mechanical axis, femoral component alignment, and tibial component alignment was 7% (112 of 1500 TKAs), 7%, and 8%, respectively, with 70% of limbs placed in excessive varus and 30% in excessive valgus. Preoperative varus deformity of more than 20° and femoral bowing of more than 5° were associated with increased risk of placing the limb mechanical axis outside the acceptable ± 3° range after computer-assisted TKA. CONCLUSIONS: The presence of preoperative radiographic risk factors should alert the surgeon to increased chance of malalignment and every measure should be undertaken in such at-risk knees to ensure proper limb and component alignment and soft tissue balance. LEVEL OF EVIDENCE: Level II, prognostic study. See Instructions for Authors for a complete description of levels of evidence